The potential of STEM-based curriculum in realizing 21st-century learning: Bibliometric analysis - W. Wahyudin; Muhammad Rafi Valliansyah; Cindy Sri Meidina Adeliani; Muhammad Bahrul Ulum (Himpunan Pengembang Kurikulum Indonesia (HIPKIN), 2024)
Education, in general, cannot be separated from various existing problems. One of these problems is a gap between graduate education and industry needs. This causes multidisciplinary learning, such as STEM, to be carried out. Extracting information related to research in the STEM curriculum field as an effort to realize 21st-century learning is important. This research aims to analyze the scope of STEM-based curriculum research in realizing 21st-century learning using a bibliometric review. Data collection was carried out through the Scopus database with the keywords (